THE ACCURACY OF EXISTING PRE-HOSPITAL TRIAGE TOOLS FOR INJURED CHILDREN IN ENGLAND–AN ANALYSIS USING TRAUMA REGISTRY AND EMERGENCY DEPARTMENT DATA. Issue 10 (7th September 2013) - Cheung, R; Ardolino, A; Lawrence, T; Bouamra, O; Lecky, F E; Berry, K; Chaudhury, A; Issa, S; Koralage, N; Lyttle, M D; Maconochie, I K
Abstract : Objectives & Background: Pre-hospital triage is becoming increasingly important as Regional Trauma Networks for children are implemented in England. The low incidence of trauma in children makes pre-hospital assessment of injury severity and where to send an injured child challenging. Currently there are few validated pre-hospital triage tools for children's trauma and no consensus on which to use. We investigate performance characteristics of pre-hospital paediatric triage tools currently in use in England for identifying injured children. Methods: We identified a total of eight pre-hospital paediatric triage tools (six in current usage in England). Each tool was interrogated using 701 retrospective clinical episodes from the Trauma Audit and Research Network (TARN–representing severely injured children) and from 2934 patient records in four English Emergency Departments (representing moderate to minor injuries). Target rates for under– and over-triage were set as <5% and <25–50% respectively. Results: From TARN data, two triage tools demonstrated acceptable under-triage rates (3% and 4%) for severe injuries but unacceptable over-triage of moderate injuries (83% and 72%). Two tools demonstrated acceptable over-triage (7% and 16%) with unacceptable under-triage (61% and 63%). Four tools demonstrated unacceptable under- and over-triage. For moderate and minor injuries, three tools demonstrated acceptable under- and over-triage rates (all 0%). The other five tools had unacceptable under-triage rates (25–100%). All eight tools had acceptable over-triage rates (1%–21%). (See tables 1 and 2 ) Conclusion: For severe injuries, none of the pre-hospital triage tools for injured children currently used in England meet recommended criteria for over- and under-triage rates. For moderate to minor injuries, all tools achieved acceptable over-triage rates but tended to under-triage. There is an urgent need for development of triage tools to accurately risk-stratify injured children in the pre-hospital setting.